The tragedy of the commons, the public goods dilemma, and the meaning of rivalry and excludability in evolutionary biology - Dionisio, F. (2006)
Problem: In the study of conflicts, both economists and evolutionary biologists use the concepts ‘tragedy of the commons’ and ‘public goods dilemma’. What is the relationship between the economist and evolutionist views of these concepts? Model features: The economics literature defines the tragedy of the commons and the public goods dilemma in terms of rivalry and excludability of the good. In contrast, evolutionists define these conflicts based on fitness functions with two components: individual and group components of fitness. Mathematical method: Evolutionary game theory and the calculation of evolutionarily stable strategy trait values by standard optimization techniques and by replacing slopes of group phenotype on individual genotype by coefficients of relatedness. Conclusion: There is a direct relationship between rivalry and the individual component of fitness and between excludability and the group component of fitness. Moreover, although the prisoner’s dilemma constitutes a suitable metaphor to analyse both the public goods dilemma and the tragedy of the commons, it gives the false idea that the two conflicts are symmetric since they refer to situations in which individuals consume a common resource – tragedy of the commons – or contribute to a collective action or common good – public goods dilemma. However, the two situations are clearly not symmetric: from the economical point of view they differ by rivalry, and from the evolutionary biology point of view the two conflicts differ by the significance of the within-group competition in the fitness function.